THE INCREASE IN COLOSTRUM SECRETION ON EARLY SKIN-TO-SKIN CONTACT ON POSTPARTUM MOTHER - Laily Yuliatun; Muladefi Choiriyah; Yulaily Riza (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2014)
Introduction. Colostrum contains a large number of protective factors providing passive and active protection to a wide variety of known pathogens. Its production could be stimulated by early skin-to-skin contact between mother and baby. Hence, this study aimed to investigate the effect of early skin-to-skin contact on the onset of colostrum secretion in postpartum mother. Methods. This study was cross sectional. The data were analyzed by Mann–Whitney test. Literate postpartum mothers, underwent pervaginam delivery in >37 weeks of gestational age with clear amniotic fluid, having baby with > 2500 gr of weight, Apgar score 6 – 8, and no congenital defects were included in this study. The onset of colostrum secretion was measured through observation sheet. 26 samples were recruited in this study. Results. The onset of colostrum secretion was faster in mother underwent early skin-to-skin contact (p=0.002). Discussion. Thus, this study suggested that early skin-to-skin contact enhanced the onset of colostrum secretion. Keywords: Early skin-to-skin contact, Colostrum, Postpartum